Tooth Contact Analysis of Discrete Involute Spherical Gear - Gao Xinghua; Liu Yang; Yang Ze; Yang Yitao; Xie Lanqiang (Jixie chuandong)
A new kind of the discrete involute spherical gear transmission mechanism is presented,this gear transmission mechanism can realize the transmission of the pitch motion,partial pendulum movement and rotary motion in the space and avoid the transmission principle error of the existing discrete spherical gear. By using the ANSYS simulation software,the tooth surface contact characteristic analysis of the discrete involute spherical gear with dividing circle diameter is 512 mm under different meshing states is carried out. It is found that,the tooth surface contact area of the discrete involute spherical gear transmission is inversely proportional with the change of meshing angle under the condition of fixed torque. And along with the meshing angle increases,the maximum contact stress action point will move toward the tip,and the maximum contact stress will increase（ up to 2. 059 3 × 106MPa）. Through studying the transmission characteristics of this kind of gear,the basis of application for the study of spatial mechanism and mechanical arm is provided.